2014
DOI: 10.1098/rstb.2013.0515
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and synaptic plasticity—a mutual relationship

Abstract: MicroRNAs (miRNAs) are rapidly emerging as central regulators of gene expression in the postnatal mammalian brain. Initial studies mostly focused on the function of specific miRNAs during the development of neuronal connectivity in culture, using classical gain-and loss-of-function approaches. More recently, first examples have documented important roles of miRNAs in plastic processes in intact neural circuits in the rodent brain related to higher cognitive abilities and neuropsychiatric disease. At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 86 publications
(158 reference statements)
1
70
0
6
Order By: Relevance
“…In addition, effective diagnosis and treatment targets for neuropathic pain are lacking. It is reported that miRNA molecules are important regulatory factors in the nervous system and are extensively involved in various physiological and pathological activities of the nervous system, such as memory, neural remodeling and neurodegenerative changes (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, effective diagnosis and treatment targets for neuropathic pain are lacking. It is reported that miRNA molecules are important regulatory factors in the nervous system and are extensively involved in various physiological and pathological activities of the nervous system, such as memory, neural remodeling and neurodegenerative changes (21).…”
Section: Discussionmentioning
confidence: 99%
“…miR-134, miR-383, miR-382, miR-182) (Cheng et al, 2014) miR-199a (Tsujimura et al, 2015) miRNAs in the activity-dependent maturation of neural circuits, a form of developmental synaptic plasticity, in the mammalian brain in vivo. Further evidence for a role of miRNAs in synaptic plasticity, both during development and in adults, has been provided in recent years (reviewed by Aksoy-Aksel et al, 2014;Olde Loohuis et al, 2012;Wang et al, 2012;Ye et al, 2016), underscoring the importance of miRNAs in correct neural circuit formation, maturation and function.…”
Section: Synapse Developmentmentioning
confidence: 99%
“…In recent years, evidence for an important role of miRNAs in adult synaptic plasticity and cognition is also accumulating. However, these studies are not the focus of this Review, and we refer the reader to recent reviews on this subject (Aksoy-Aksel et al, 2014;Olde Loohuis et al, 2012;Wang et al, 2012;Ye et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Karpova et al in a review focused on the epigenetic control of the brain-derived neurotrophic factor (BDNF), a central player in neuronal plasticity, reported that miRNAs, such as miR-206, targeted BDNF transcripts resulting in memory impairment and were up-regulated in neurodegenerative disorders [129]. Several reviews summarize the regulatory mechanisms of miRNAs in synaptic plasticity and learning memory and the picture that emerges is that miRNAs are ideally suited to contribute to the regulation of long-term potentiation-related gene expression, that miRNAs are pleiotropic, synaptically located, tightly regulated, and function in response to synaptic activity [130]–[133]. The first direct links between miRNA dysfunction and synaptic pathologies are emerging, raising the interest in these molecules as potential biomarkers and therapeutic targets in NDD.…”
Section: Evs Released By Brain Cells Contain Mirnas Which Are Invomentioning
confidence: 99%